KBTBD13 is an actin-binding protein that modulates muscle kinetics - de Winter, Josine M.; Molenaar, Joery P.; Yuen, Michaela; van der Pijl, Robbert; Shen, Shengyi; Conijn, Stefan; van de Locht, Martijn; Willigenburg, Menne; Bogaards, Sylvia J.P.; van Kleef, Esmee S.B.; Lassche, Saskia; Persson, Malin; et al. (The Journal of Clinical Investigation, 2024)
The mechanisms that modulate the kinetics of muscle relaxation are critically important for muscle function. A prime example of the impact of impaired relaxation kinetics is nemaline myopathy caused by mutations in KBTBD13 (NEM6). In addition to weakness, NEM6 patients have slow muscle relaxation, compromising contractility and daily life activities. The role of KBTBD13 in muscle is unknown, and the pathomechanism underlying NEM6 is undetermined. A combination of transcranial magnetic stimulation–induced muscle relaxation, muscle fiber– and sarcomere-contractility assays, low-angle x-ray diffraction, and superresolution microscopy revealed that the impaired muscle-relaxation kinetics in NEM6 patients are caused by structural changes in the thin filament, a sarcomeric microstructure. Using homology modeling and binding and contractility assays with recombinant KBTBD13, Kbtbd13-knockout and Kbtbd13R408C-knockin mouse models, and a GFP-labeled Kbtbd13-transgenic zebrafish model, we discovered that KBTBD13 binds to actin — a major constituent of the thin filament — and that mutations in KBTBD13 cause structural changes impairing muscle-relaxation kinetics. We propose that this actin-based impaired relaxation is central to NEM6 pathology.